Draw Point Construction Improvement Using Six Sigma - Basri, Mursyid Hasan; Mulyanto, Rahmat (Jurnal Manajemen Teknologi, 2009)
Draw point is a loading pointh beneath a stope, utilizing gravity to move down bulk material in underground mine block caving of PT Freeport Indonesia. A draw point is a steel set that is erected and poured in place with concrete. There are 9 sub processes of draw point construction: site preparation, lean concrete, embedded rail, concrete floor, anvil top, lintel set, forming & meshing, wall & roof concrete, stripping & general clean-up. Based on data analysis period 2008, there is a gap 4.03 until draw point of yearly target with average of completion time of a draw point construction 46.44 shifts and standard deviation 6.95 shifts. It is slower by 9.7% of target 42 shifts. The high standard deviation and slower process indicate there is a process quality problem in draw point construction so it makes draw point construction incompliance to achieve its monthly or yearly target. For improving the process quality, Six Sigma approach with DMAIC methodology will be used to indentify incapable process and its causes. Then alternative solutions are proposed to fix it and control the key process variable causing the defects.Keywords:completion time, process quality, six sigma, DMAIC